1993
DOI: 10.1007/bf01658939
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant chemotherapy for high‐grade advanced gastric cancer

Abstract: Fifty-five patients with high-grade advanced gastric cancer in whom the presence of stage IV was confirmed by preoperative diagnostic imaging were treated with PMUE therapy by a combined use of cisplatin (CDDP) 75 mg/m2, mitomycin C (MMC) 10 mg/body, etoposide 150 mg/body, and UFT (a combination of 1-(2-tetrahydrofuryl)-5-fluorouracil and uracil in a molar ratio of 1:4) 400 mg/day. CDDP and MMC was administered intravenously on the first day, followed by etoposide 50 mg/day on the 3rd, 4th, and 5th days. All t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
80
0
2

Year Published

1995
1995
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(85 citation statements)
references
References 16 publications
(20 reference statements)
1
80
0
2
Order By: Relevance
“…Although patients with this disease have been treated after surgical resection with high-dose systemic or intraperitoneal chemotherapy, the results of these treatments have been poor, and most patients with peritoneal dissemination die within 6 months after diagnosis [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although patients with this disease have been treated after surgical resection with high-dose systemic or intraperitoneal chemotherapy, the results of these treatments have been poor, and most patients with peritoneal dissemination die within 6 months after diagnosis [1].…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of gastric cancer patients with peritoneal dissemination is extremely poor [1]. For that reason, various clinical attempts have been made to treat the peritoneal dissemination of gastric cancer, including systemic chemotherapy [2], intraperitoneal chemotherapy and/or hyperthermia [3], and aggressive surgery [4].…”
Section: Introductionmentioning
confidence: 99%
“…
dissemination still have a poor prognosis [1]; most of these patients die within 6 months of diagnosis, while the 5-year survival rate is nil [2,3].The recent introduction of an oral drug, S-1, has increased the overall response rates (ORRs) to 44% and 49% and median survival time (MST) to 8 months in phase II studies [4,5].Several reports have demonstrated that S-1 was effective for undifferentiated histological types, such as poorly differentiated adenocarcinoma and signet-ring cell carcinoma, which are relevant to peritoneal dissemination [6]. S-1 has been reported to be effective in prolonging the survival of gastric cancer patients with peritoneal dissemination [4][5][6][7].

Moreover, S-1 in combination with other anticancer drugs such as cisplatin (CDDP), taxanes, and irinotecan (CPT-11) increased ORRs and prolonged MST [8][9][10][11].

Paclitaxel is a cytotoxic antineoplastic agent that causes excessive polymerization of tubulin and microtubule dysfunction, resulting in tumor cell death [12].

…”
mentioning
confidence: 99%
“…It has been reported that some patients who received intensive neoadjuvant chemotherapy could not be operated on due to severe toxicity [33,34]. While S-1 is effective for recurrent gastric cancer, it is expected to be useful as neoadjuvant chemotherapy because of its mild toxicity.…”
Section: Discussionmentioning
confidence: 99%